Law, Society and Tax Law Enforcement in a Sharia Context - Fajrin Mubarokah Parhani; Dony Septriana Rosady; Titi Ratna Garnasih; Eka Juarsa; Siah Khosyi'ah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The paper "Law, Society, and Tax Law Enforcement in a Sharia Context" comprehensively explores the intersection between Islamic legal principles, the social structure of society, and tax law enforcement practices. The research focuses on how Islamic law views and regulates tax collection, highlighting the balance between the fiscal needs of the state and moral obligations towards society. With a multidisciplinary approach, this paper examines the impact of tax regulations on social and economic life, as well as how sharia principles can be applied to create a fair and efficient taxation system. The study provides insights into how tax law enforcement is regulated in Islamic sharia, as well as the challenges and opportunities that arise in its implementation in contemporary society.